Native video in HTML5 - Griffiths, David, 1969- (O'Reilly breakdown., 2010)
"There's probably nothing bigger in the HTML5 landscape than the new video tag. You can play videos without having to use Flash or embed code, and that means your videos are playable on more browsers and more devices. In this video, HTML5 guru David Griffiths shows you the ins and outs of creating a video and then accessing that video's properties through JavaScript."--Resource description page.